EKSISTENSI REGULATORY SANDBOX OJK DALAM PENGEMBANGAN INOVASI FINTECH DI INDONESIA - Imam Fathwa; Hasnah Aziz; Bayu Triwibowo; Tri Susanto; Ratu Chumairoh Noor (Berajah Journal, 2026)
The development of financial technology (fintech) in Indonesia has resulted in significant transformation in the financial services ecosystem, but has simultaneously raised complex regulatory challenges because the speed of technological innovation outpaces the ability of existing legal frameworks to adapt. The Financial Services Authority responded to this challenge through the implementation of a regulatory sandbox as a regulatory mechanism that allows testing of fintech innovations in a controlled environment before full implementation. This article aims to analyze juridically the existence of the OJK regulatory sandbox in the development of fintech innovation in Indonesia. The research method used is qualitative with a normative-empirical legal approach. Data was collected through studies of legislation, OJK policies, regulatory sandbox testing reports, and scientific literature studies. The results show that the existence of the OJK regulatory sandbox has a strategic role in encouraging fintech innovation while maintaining financial system stability and consumer protection, but faces juridical challenges including weak legal foundations that are not explicitly regulated in law, ambiguity in OJK authority in implementing regulatory sandboxes, and limited consumer protection and dispute resolution mechanisms during the testing period. This article recommends the need to enrich the juridical foundation of regulatory sandboxes through revision of laws or government regulations, affirmation of proportional OJK authority, and development of comprehensive consumer protection mechanisms to create a fintech ecosystem that is innovative and fair.